‘Vialfas’, a new late blooming almond cultivar - Socias i Company R.; Alonso J.M.; Kodad O.; Ansón J.M. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The almond breeding programme of the CITA of Aragón aims at late-blooming cultivars with good horticultural behaviour, self-compatible, and with good kernel quality. After previous releases, ‘Vialfas’ responds to most of these objectives. This new release (selection I-3-27, clone 546) comes from the cross ‘Felisia’ × ‘Bertina’. Its blooming time is very late, three days before ‘Mardía’ on the average, with similar chilling requirements than ‘Mardía’ but with slightly lower heat requirements which could explain the difference in blooming time. Flowers are of mean size, white, with peristigmatic style. Bloom density is high and consistent. It is selfcompatible (genotype SfiS11), of high fruit set and resistance to frosts. Nuts are of mean size (4.7 g), as well as kernels (1.2 g), with a low shelling percentage (25%) and hard shell, and early ripening. Kernel composition is average for protein (18.84% of dry matter), oil (56.72%), and tocopherols (251.8 g/kg oil), and phytosterols (2589 mg/kg oil), but very high for oleic acid (78% of total oil). The tree is slightly upright, with relative tolerance to disease and highly productive.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)